2022
DOI: 10.1007/s00417-022-05696-5
|View full text |Cite
|
Sign up to set email alerts
|

Elongation of the inferior rectus tendon with fascia lata graft for large vertical squint angles in patients with Graves’ orbitopathy

Abstract: Purpose To investigate the use of fascia lata (FL) grafts for inferior rectus muscle (IRM) tendon elongation in patients with large vertical squint angles with Graves’ orbitopathy (GO). Methods In this retrospective study, we included a consecutive series of 20 eyes of 13 patients with GO who underwent IRM tendon elongation with FL. Orthoptic and ophthalmologic examinations including measurement of the head posture, the extent of deviation in primary posit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Some specialists have tried using the oblique muscles instead of the medial or lateral recti, [ 39 ] while other specialists studied alternatives aside from utilizing real muscle such as fascia lata especially in patients with complex ocular motility disorders like thyroid eye disease [ 40 ] and congenital innervation disorders for which conventional strabismus surgery is insufficient. Surgery with tendon elongation allows correction of larger angles and is able to maintain a sufficient arc of contact for rectus muscles.…”
Section: Discussionmentioning
confidence: 99%
“…Some specialists have tried using the oblique muscles instead of the medial or lateral recti, [ 39 ] while other specialists studied alternatives aside from utilizing real muscle such as fascia lata especially in patients with complex ocular motility disorders like thyroid eye disease [ 40 ] and congenital innervation disorders for which conventional strabismus surgery is insufficient. Surgery with tendon elongation allows correction of larger angles and is able to maintain a sufficient arc of contact for rectus muscles.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, allogenous FL grafts avoid harvest site morbidities [ 37 ]. To date, no relevant host reaction or absorption of the allogenous FL grafts have been reported, which minimizes the possibility of significant over- or under-correction of the LER [ 21 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…In 1909, Payr pioneered the use of FL in ophthalmic surgery for the correction of congenital ptosis [ 28 ]. Since then, FL has been used for the treatment of numerous ophthalmic conditions, such as orbital implant extrusion, scleromalacia perforans, cicatricial entropion, and large vertical squint angles in patients with Graves’ orbitopathy [ 21 , 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…Other groups have also reported satisfactory results ( 140 , 141 ). To reduce IR muscle restriction, tendon elongation uses homologous scleral grafts, polytetrafluoroethylene (Goretex), silicone, bovine pericardium, ( 142 ), or fascia lata ( 143 ). Jefferis et al ( 127 ) reported favorable outcomes after prioritizing downgaze alignment (rather than primary gaze alignment) to avoid downgaze diplopia.…”
Section: Squint Surgerymentioning
confidence: 99%